2001
DOI: 10.1176/appi.ajp.158.4.594
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Prediction of Posttraumatic Stress Disorder Symptoms in Severely Injured Accident Victims

Abstract: In severely injured accident victims who were healthy before experiencing trauma, the incidence of PTSD was low. One-third of the variance of PTSD symptoms at 1-year follow-up could be predicted by mainly psychosocial variables.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
133
6
14

Year Published

2003
2003
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 227 publications
(169 citation statements)
references
References 36 publications
16
133
6
14
Order By: Relevance
“…Nach 6 Monaten werden noch in 5-25% posttraumatische Belastungsstörungen beobachtet (Brom et al 1993;Feinstein and Dolan 1991;Mayou et al 1993;Ursano et al 1999). Auch im längerfristigen Verlauf wurden ähnliche Inzidenzraten beschrieben (Koren et al 1999;Malt 1988;Malt et al 1989;Mayou et al 2001;Schnyder et al 2001a). Fünf Jahre nach einem Unfall haben immerhin noch 8% eine chronische posttraumatische Belastungsstörung (Mayou et al 1997).…”
Section: Zur Häufigkeit Posttraumatischer Belastungsstörungen Nach Ununclassified
See 2 more Smart Citations
“…Nach 6 Monaten werden noch in 5-25% posttraumatische Belastungsstörungen beobachtet (Brom et al 1993;Feinstein and Dolan 1991;Mayou et al 1993;Ursano et al 1999). Auch im längerfristigen Verlauf wurden ähnliche Inzidenzraten beschrieben (Koren et al 1999;Malt 1988;Malt et al 1989;Mayou et al 2001;Schnyder et al 2001a). Fünf Jahre nach einem Unfall haben immerhin noch 8% eine chronische posttraumatische Belastungsstörung (Mayou et al 1997).…”
Section: Zur Häufigkeit Posttraumatischer Belastungsstörungen Nach Ununclassified
“…Die emotionalen und kognitiven Reaktionen, die bei den Betroffenen während und unmittelbar nach dem Unfall ablaufen, spielen eine entscheidende Rolle für die Traumaverarbeitung: Die subjektiv erlebte Bedrohung, die oft keineswegs mit den objektiven Unfall-und Verletzungsparametern korreliert, ist einer der robustesten Prädiktoren für die Entstehung der posttraumatischen Belastungsstörung (Blanchard et al 1995;Liegey Dougall et al 2001;Mayou et al 2001;Schnyder et al 2001a). Andererseits haben Patienten, die die Verantwortung für den Unfall sich selber zuschreiben, ein geringeres Risko, später an einer posttraumatischen Belastungsstörung zu erkranken (Delahanty et al 1997;Hickling et al 1999).…”
Section: Früherkennung: Worauf Muss Der Chirurg Achten?unclassified
See 1 more Smart Citation
“…Acute-care based studies to date have identified several predictors of PTSD that are accessible in the early aftermath of trauma exposure, including lifetime trauma exposure, disadvantaged socio-demographic background, event severity, and early PTSD symptoms (Ehlers, Mayou, & Bryant, 2003; Freedman, Brandes, Peri, & Shalev, 1999; Karstoft, Galatzer-Levy, Statnikov, Li, & Shalev, 2015; Schnyder, Moergeli, Klaghofer, & Buddeberg, 2001; Shah & Vaccarino, 2015; Shalev, Freedman, Peri, Brandes, & Sahar, 1997; Shalev, Peri, Canetti, & Schreiber, 1996). However, differences in the design, location, sampling, measurements, and length of follow-up of these studies has precluded the development of a generalizable predictive model (Bryant, Creamer, O’Donnell, Silove, & McFarlane, 2012; Bryant et al, 2015; Ehlers, Mayou, & Bryant, 1998; Heron-Delaney, Kenardy, Charlton, & Matsuoka, 2013; Schnyder et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…However, differences in the design, location, sampling, measurements, and length of follow-up of these studies has precluded the development of a generalizable predictive model (Bryant, Creamer, O’Donnell, Silove, & McFarlane, 2012; Bryant et al, 2015; Ehlers, Mayou, & Bryant, 1998; Heron-Delaney, Kenardy, Charlton, & Matsuoka, 2013; Schnyder et al, 2001). …”
Section: Introductionmentioning
confidence: 99%